Effect of MUC2 Antisense Oligodeoxynucleotide on Cell Proliferation, Adhesion, and Proteolytic Enzyme in Human Gastric Carcinoma in vitro - 杨雅莹 易永芬 张晓燕 肖春卫 林晓 周文文 (Chinese journal of cancer research, 2007)
Objective：To investigate the effect of MUC2 antisense oligodeoxynucleotide （ASODN） on cell proliferation, adhesion and proteolytic enzyme inhuman gastric carcinoma cell line （SGC7901）. Methods： Phosphorothioate MUC2 ASODN was synthesized and packaged by lipofectin, and then transfected to SGC7901 cells. The expression of MUC2 mRNA and protein after transfection was detected by reverse transcription-polymerase chain reaction （RT-PCR） and immunohistochemical method respectively, and the effect of MUC2 ASODN on cell proliferation, adhesion and proteolytic enzyme was determined by flow cytometry（FCM）, MTT method, Rose Bengal and immunohistochemical method. Results： Compared with the blank control group, ASODN efficiently downregulated the expression of MUC2 mRNA and protein in SGC7901 cells 48h after transfection（P〈0.01）. Various concentrations of ASODN could significantly inhibit the growth of SGC7901, and the inhibition peaked at the 48th hour after transfection（P〈0.05）. The apoptosis rate of the experimental group was about 4.38%, and the percentage of S-phase cells rose while G0/G1-phase cells fell because most of them were blocked at S-phase. In addition, cells treated with MUC2 ASODN showed lower adhesion ability with matrix and endothelial cells than control cells in vitro（P〈0.01）. By immunohistochemical method, the upregulation of E-cadherin proteins and the downregulation of MMP2 and cathepsinD proteins were also observed（P〈0.05）. Conclusion： MUC2 ASODN could efficiently inhibit SGC7901 cell proliferation, reduce cell adhesion ability and downregulate the expression levels of proteolytic enzyme in vitro.